2022
DOI: 10.22336/rjo.2022.54
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuropathies post-Covid 19 - review

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
4
0
2
Order By: Relevance
“…A literature review confirmed a few cases of NAION in patients with SARS-CoV-2 infection [ 15 ]. However, a definite association between NAION and COVID-19 vaccination has not been reported to date [ 13 , 16 ]. Patients with COVID-19 may develop a state of hypercoagulability and hypoxemia, critical aspects that may play a role in the development of NAION, a circulatory insufficiency disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review confirmed a few cases of NAION in patients with SARS-CoV-2 infection [ 15 ]. However, a definite association between NAION and COVID-19 vaccination has not been reported to date [ 13 , 16 ]. Patients with COVID-19 may develop a state of hypercoagulability and hypoxemia, critical aspects that may play a role in the development of NAION, a circulatory insufficiency disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous retrospective studies have described a prothrombotic condition in many patients with COVID-19 [ 10 - 12 ]. This hypercoagulable state likely contributes to an increased risk of developing NAION in some COVID-19 patients [ 13 , 14 ]. This clinicopathological case report describes a post-menopausal patient who experienced sudden, painless inferotemporal visual field loss after a COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Оптические нейропатии относятся к одному из обширных разделов офтальмологии, имеют множественные этиопатогенетические механизмы, иногда непредсказуемое течение, сопровождаясь порой необратимыми осложнениями. Нейротропный и нейроинвазивный характер вируса SARS-CoV-2 был подтвержден в том числе поражением зрительного нерва у инфицированных пациентов [13]. Нейроофтальмологические проявления коронавирусной инфекции встречаются редко, и в настоящее время описаны немногочисленные клинические случаи вовлечения зрительного нерва в патологический процесс.…”
Section: Discussionunclassified
“…Furthermore, proning protocols (in the position of patients in respiratory distress in their stomachs) have been associated with ischemic optic neuropathy and visual loss, again highlighting the importance of physical examination and pressure redistribution in minimizing iatrogenic injuries in ventilated patients with COVID-19. 144 …”
Section: Ophthalmological Symptoms In the Course Of Covid-19mentioning
confidence: 99%